1999
DOI: 10.1088/0031-9155/44/5/314
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the equivalent whole-body dose during radiation therapy by cytogenetic methods

Abstract: Estimates of equivalent whole-body dose following partial body exposure can be performed using different biophysical models. Calculations should be compared with biodosimetry data, but measurements are complicated by mitotic selection induced in target cells after localized irradiation. In this paper we measured chromosomal aberrations in peripheral blood lymphocytes during radiotherapy, and estimated the equivalent whole-body dose absorbed, by using the novel technique of interphase chromosome painting. Prema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…As previously described, the yield of dicentrics and rings increased with the tumour dose for each patient but with substantial interindividual variability [24][25][26]. In agreement with other studies, a strong correlation between the size of irradiation field and the yield of chromosome aberrations was found [12,26,27]. This ''volume effect'' may result from an increasing number of lymph nodes and/ or blood vessels included in the field of irradiation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As previously described, the yield of dicentrics and rings increased with the tumour dose for each patient but with substantial interindividual variability [24][25][26]. In agreement with other studies, a strong correlation between the size of irradiation field and the yield of chromosome aberrations was found [12,26,27]. This ''volume effect'' may result from an increasing number of lymph nodes and/ or blood vessels included in the field of irradiation.…”
Section: Discussionsupporting
confidence: 90%
“…The same variability in the rate of damage induced in lymphocytes during radiotherapy has been observed in other studies that used different measurements, such as premature chromosome condensation (PCC), micronuclei or c-H2AX foci [12][13][14]. Explanations for these interpatient differences have suggested that damage yields after fractionated partialbody exposure do not depend only on the dose delivered locally, but may be also influenced by many other parameters, including individual variability in the response to ionising radiation, target field size or tumour localisation [9,10,12]. In fact, fractionated radiotherapy is a typical example of non-uniform exposure.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Planning target area was approximately 200 cm 2 for all patients. Based on in vitro dose-response curves for the induction of chromosome-type exchanges in human lymphocytes, the effective whole-body dose equivalent for these patients at the end of the treatment was around 2 Sv (Durante et al, 1999). Further details concerning patients treated with Xrays (Durante et al, 1999) or C-ions have been already reported elsewhere.…”
Section: Patientsmentioning
confidence: 94%
“…Cytogenetic procedures have been previously provided in detail both for astronauts (George et al, 2001;Greco et al, 2003) and for cancer patients (Durante et al, 1999). Briefly, blood samples were collected before and after space flight (astronauts) or before and after the radiotherapy course (patients) and grown for 48 h at 37°C in RPMI medium supplemented with 20 % serum and 1 % phytohemagglutinin.…”
Section: Chromosome Analysismentioning
confidence: 99%